Odpowiedź :
a) 5x - 3 = 12
5x = 12 + 3
5x = 15 /: 5
x = 3
b) 5x + 4 - 2x = 13
3x = 9 /: 3
x =3
c) 3x - 5 - x = 11
2x = 16 /: 2
x = 8
d) x - 5 + 6x = 16
7x = 21 /: 7
x = 3
e) 4x + 7 = 15
4x = 8/: 4
x = 2
5x-3=12
5x=12+3
5x=15 /:5
x=3
5x+4-2x=13
5x-2x=13-4
3x=9 /:3
x=3
3x-5-x=11
3x-x=11+5
2x=16 /:2
x=8
x-5+6x=16
x+6x=16+5
7x=21 /:7
x=3
4x+7=15
4x=15-7
4x=8 /:4
x=2
Mam nadzieje że pomogłam i będę wdzięczna są naj!
5x=12+3
5x=15 /:5
x=3
5x+4-2x=13
5x-2x=13-4
3x=9 /:3
x=3
3x-5-x=11
3x-x=11+5
2x=16 /:2
x=8
x-5+6x=16
x+6x=16+5
7x=21 /:7
x=3
4x+7=15
4x=15-7
4x=8 /:4
x=2
Mam nadzieje że pomogłam i będę wdzięczna są naj!